Pertumbuhan Padi Varietas Ciherang Setelah Diinokulasi dengan Azospirillum Mutan Multifungsi - Listanto, Edy; Riyanti, Eny Ida (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2016)
Modern agriculture is very closely related to the application of fertilizer to induce plants grow. The application of bio-fertilizers is expected to reduce the negative impact of chemical fertilizers. The purpose of this study was to determine the effect of multi-functional Azospirillum N2 fixation, P solubility and IAA production on the growth of Ciherang rice in pot experiment in greenhouse BB Biogen. The experiment treatment were 3 types of inoculation (non-inoculation, inoculation using wildtype Aj Bandung 6.4.1.2 and the mutant isolate of AJM 3.7.1.14 ), and 4 levels of fertilizer application (non-fertilization, a quarter dose, a half dose, and the real dose of fertilization on rice in lowland). The Azospirillum isolates were used wildtype isolate Aj Bandung 6.4.1.2 and mutant isolate AJM 3.7.1.14 that was isolated and mutated using ethyl methanesulfonate (EMS) in BB Biogen. Seeds of Ciherang rice were inoculated using Azospirillum at cell density 106 cell/ml in different seedling tray. After 14 days, the seedlings were transferred to planting pots which consist of 3 plants per pot. Parameters observed were plant height, number of tillers, number of panicles per hill, wet and dry weight of panicles per hill, weight of 100 seeds, N and P content of the stover. The results showed that both wild-Azospirillum and mutant inoculum had no effect on the vegetative growth of Ciherang, but showed significant effect on the number of panicle per hill, grain weight per hill and dry weight of seeds per panicle. The use of Azospirillum and N fertilizer combination affected the growth and rice yields, also reduced chemical fertilizer application.